UJI PENGERINGAN BIJI JAGUNG (Zea mays. Sp) MENGGUNAKAN ALAT PENGERING BIJI BIJIAN TIPE RAK (TRAY DRYER) - Rahmat, Muliawan; Patang, Patang; Rais, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2019)
This study aims to determine the mechanism and effect of drying corn kernels using a grain dryer (Tray Dryer). This research is a type of experiment research consisting of 2 variables. Variable A is temperature with 3 variable levels (60 ° C, 65 ° C, 70 ° C) and variable B is drying time with 3 variable levels (3 hours, 4 hours and 5 hours). The research sample is corn seed off harvest with an initial water content of 21.1% dried using a rack-shaped dryer (Tray dryer). To find out the temperature changes that occur, the drying process is measured by the temperature of the drying chamber and the temperature of corn kernels using a thermometer. Before and after drying the water content was measured to determine the changes in corn seed moisture content of each treatment used. The results showed that the higher the temperature and the length of the drying process will cause the drying rate to be faster and the decrease in water content will be smaller or slower.